Comparison Of Kiln-Derived And Gasifier-Derived Biochars As Soil Amendments In The Humid Tropics - Deal, Christopher; Brewer, Catherine E.; Brown, Robert C.; Okure, Mackay A.E.; Amoding, Alice (Biomass and Bioenergy, 2012)
Biochar is the carbonaceous solid byproduct from thermal treatment of biomass that is produced specifically for application to soils. Studies have shown that when biochar is added to soils, it is able to increase yields, improve soil properties, and effectively store carbon for hundreds to thousands of years. This study compared the performance of biochar from five different feedstocks (coffee husks, maize cobs, eucalyptus wood, groundnut shells, and rice husks) produced in a traditional kiln and biochar from two different feedstocks (maize cobs and eucalyptus wood) produced in a downdraft gasifier. This research, conducted at Makerere University in Kampala, Uganda, was aimed at investigating the potential of biochar as a soil amendment in the humid tropics. Biochar samples were combined with undisturbed soil in a 45-day pot experiment to compare effects on maize growth. On average, soils amended with gasifier-produced biochar had higher yields than the unamended soil and soils amended with kiln-produced biochar. Comparing kiln-produced chars from different feedstocks, the coffee husk chars were the most productive. Results indicated that the soluble ash content of the biochar had the greatest influence on soil productivity. Ugandan soils, like most soils in the humid tropics, are strongly acidic (pH = 4.7), and the increase in pH caused by the soluble ash in the biochar provided for more favorable growing conditions and higher nutrient availability.
Keywords: Biochar;Pyrolysis;Gasification;Tropics;Soil pH;Ash